IL-10 and socs3 Are Predictive Biomarkers of Dengue Hemorrhagic Fever - Lilian Karem Flores-Mendoza; Tania Estrada-Jiménez; Virginia Sedeño-Monge; Margarita Moreno; María del Consuelo Manjarrez; Guadalupe González-Ochoa; Lourdes Millán-Pérez Peña; Julio Reyes-Leyva (Mediators of Inflammation)
Background. Cytokines play important roles in the physiopathology of dengue infection; therefore, the suppressors of cytokine signaling (socs) that control the type and timing of cytokine functions could be involved in the origin of immune alterations in dengue. Objective. To explore the association of cytokine and socs levels with disease severity in dengue patients. Methods. Blood samples of 48 patients with confirmed dengue infection were analyzed. Amounts of interleukins IL-2, IL-4, IL-6, and IL-10, interferon- (IFN-) γ, and tumor necrosis factor- (TNF-) α were quantified by flow cytometry, and the relative expression of socs1 and socs3 mRNA was quantified by real-time RT-PCR. Results. Increased levels of IL-10 and socs3 and lower expression of socs1 were found in patients with dengue hemorrhagic fever (DHF) with respect to those with dengue fever (DF) (p<0.05). Negative correlations were found between socs1 and both IL-10 and socs3 (p<0.01). The cutoff values of socs3 (>199.8-fold), socs1 (<1.94-fold), and IL-10 (>134 pg/ml) have the highest sensitivity and specificity to discriminate between DF and DHF. Conclusion. Simultaneous changes in IL-10 and socs1/socs3 could be used as prognostic biomarkers of dengue severity.